2019
DOI: 10.1007/s00210-019-01779-z
|View full text |Cite
|
Sign up to set email alerts
|

cGMP: a unique 2nd messenger molecule – recent developments in cGMP research and development

Abstract: Cyclic guanosine monophosphate (cGMP) is a unique second messenger molecule formed in different cell types and tissues. cGMP targets a variety of downstream effector molecules and, thus, elicits a very broad variety of cellular effects. Its production is triggered by stimulation of either soluble guanylyl cyclase (sGC) or particulate guanylyl cyclase (pGC); both enzymes exist in different isoforms. cGMP-induced effects are regulated by endogenous receptor ligands such as nitric oxide (NO) and natriuretic pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 97 publications
(86 reference statements)
0
80
0
Order By: Relevance
“…Kinase-G also promotes phosphorylation of protein G in smooth muscle cells, which connects seven regions of transmembrane receptors and phospholipases. It then thereby inhibits ligand-receptor interaction and contractile signal transmission, enhancing relaxation of smooth muscle cells and promoting local blood flow [ 35 , 36 ]. In addition, NO is also involved in the metabolic pathways of nitrosothiol (RSNO).…”
Section: Role Of No In Lungsmentioning
confidence: 99%
“…Kinase-G also promotes phosphorylation of protein G in smooth muscle cells, which connects seven regions of transmembrane receptors and phospholipases. It then thereby inhibits ligand-receptor interaction and contractile signal transmission, enhancing relaxation of smooth muscle cells and promoting local blood flow [ 35 , 36 ]. In addition, NO is also involved in the metabolic pathways of nitrosothiol (RSNO).…”
Section: Role Of No In Lungsmentioning
confidence: 99%
“…In essence, the broad number of compound and use-patent applications in the field of sGC agonists underlines the hope that modulation of cGMP signaling with this unique mode of action holds promise for a broad number of patients in cardiovascular diseases and beyond [94].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Phosphodiesterases (PDEs) are responsible for cGMP degradation. Their increase impairs vasodilation and increases stiffness, blood pressure, hypertrophy, and inflammation [4,5]. During aging the metabolic balance turns toward cGMP degradation, and it has been shown that acute inhibition of PDE improves vasodilation in aged blood vessels [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…PDEs form a family of enzymes that degrade the substrates cAMP, cGMP, or both. There are 11 PDE subtype families (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), and each member displays tissue and substrate specificity [9]. PDE5 is expressed in vascular smooth muscle cells (VSMC), where it plays a key role in regulation of cGMP, for which it is substrate-specific.…”
Section: Introductionmentioning
confidence: 99%